Como tecnologias de software impactam no cotidiano de pessoas com autismo no Brasil: Um survey - Sousa, Tamires A. S.; Ferreira, Verilene D.; Marques, Anna Beatriz dos S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Autistic Spectrum Disorder (ASD) is characterized by persistent deficits in communication and social interaction, restrictive and repetitive patterns of behavior. The development of information systems for supporting the treatment of ASD has been intensified in recent years, allowing new ways of treatment. Although new systems are developed, there are still few studies that investigate the impact on the use of these systems on the daily of autistic users. In this sense, we conducted a research to investigate the impact on the use of information systems by autistic users. Our methodology adopted the following steps: 1) immersion in groups of social networks in which discussions about ASD are carried out; 2) identification of the research target audience; 3) creation of the research collection instrument; 4) execution of a survey with parents and professionals that care of autistic children; 5) analysis of the data obtained. During two weeks, we obtained 53 questionnaire responses. We observed that 96.2% of the respondents indicate that their children have access to software technologies and 90.5% agree that the technologies can support the teaching and learning of autistic people. We identified positive and negative characteristics of software technologies in order to provide opportunities for improving the existing systems or developing systems more adequate to needs of autistic children.